Foreign Consortium Institution and the Economic Dependency of Indonesia during the New Order: From IGGI to CGI - Noor Naelil Masruroh; Haryono Rinardi (Department of History, Faculty of Humanities, Diponegoro University, 2022)
The main purpose of this article is to analyze the economic dependency of Indonesia on sources of foreign loan funds. The problems were analyzed through the historical method based on the primary sources such as annual report from World Bank and the Indonesian Ministry of Finance. IGGI and CGI claimed to be able to support Indonesia to break away from the shackles of financial problems. Both institutions rescheduled the debt of Indonesia to the creditor countries and opened networking access of international donor from the government, private, or international donor institutions such as World Bank and IMF in two mechanisms long-term and short-term. Short term was provided to Indonesia to give space in funding import commodity, while the long-term was used to fund investment and infrastructure program. The high level of dependency made Indonesia's debt difficult to break away and the amount piled up. Indonesia's economic policy in the New Order was considered as a disaster that had an enormous effect until today.